PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Sektor Manufaktur Di Bursa Efek Indonesia) - Zulvina, Desi; Kirmizi, Kirmizi; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the influence of managerial ownership, institutional ownership, and foreign ownership on firm value with the corporate social responsibility disclosure as an intervening variable. The study was conducted on issuers manufacturing in Indonesia Stock Exchange-listed in 2012- 2014. The sample is determined by purposive sampling method. Manufacturing of all issuers listed, which obtained 36 samples. Analysis technique use multiple regressions with two steps using by SPSS version 17. The results showed that: ownership structure has an affect on the corporate social responsibility disclosure simultaneously; managerial ownership has not affect on CSR disclosure partially; institutional ownership has no effect on CSR disclosure partially; foreign ownership has no effect on CSR disclosure partially; ownership structure and corporate social responsibility disclosures have affect on firm value simultaneously; managerial ownership has affect on firm value partially; institutional ownership has no effect on firm value partially; foreign ownership has an affect on firm value partially; and the CSR disclosure has no affect on firm value partially.Keywords : Managerial Ownership, Institutional Ownership, Foreign Ownership, Disclosure of Corporate Social Responsibility, Firm Value (Tobin's Q)